Intercomparison of Ambient Nitrous Acid Measurements in a Shanghai Urban Site - Zhenni Yang; Meng Wang; Yanping Hou; Yucun Liu; Satheesh Chandran; Ravi Varma; Shengrong Lou; Jun Chen (Atmosphere, 2022)
Nitrous acid (HONO) is the major source of OH radicals in polluted regions and plays a key role in the nitrogen cycle of the atmosphere. Therefore, accurate measurements of HONO in the atmosphere is important. Long Path Absorption Photometer (LOPAP) is a common and highly sensitive method used for ambient HONO measurements. Incoherent Broadband Cavity Enhanced Absorption Spectroscopy (IBBCEAS) is a recent alternative for the detection of HONO with high temporal and spatial resolutions, which has shown a detection limit of 0.76 ppbv at a sampling average of 180 s. In this study, LOPAP and IBBCEAS-HONO instruments were deployed in a Shanghai Urban Site (Shanghai Academy of Environmental Sciences) and simultaneously recorded the data from both instruments for a quantitative intercomparison of the measured atmospheric HONO for four days from 30 December 2017–2 January 2018. The HONO concentration measured by IBBCEAS and LOPAP were well matched. The campaign average concentrations measured by IBBCEAS and LOPAP were 1.28 and 1.20 ppbv, respectively. The intercomparison results demonstrated that both the IBBCEAS-HONO instrument and LOPAP-HONO instrument are suitable for ambient monitoring of HONO in a polluted urban environment.